تقدير قوة الهجين والمقدرة على الائتلاف لصفة الإنتاجية وبعض مواصفات الثمار في الفليفلة Capsicum annum L.)). - خوجه, حسان; محمد, ردينة (Latakia University Journal -Biological Sciences Series, 2017)
أجريت الدراسة في مزرعة خاصة في محافظة طرطوس خلال الفترة 2013-2014.تم تهجين خمسة أصناف من الفليفلة بطريقة التهجين نصف المتبادل( half diallel crosses)؛ لتقدير قوة الهجين لعشرة هجن قياساً لمتوسط الأبوين ولأفضلهما, ولحساب مقدرة الائتلاف العامة للآباء، والخاصة للهجن الناتجة عنها، وذلك لمؤشراتالإنتاجية الكلية وبعض مواصفات الثمار.أظهرت النتائج تميز أغلب الهجن بقوة هجين عالية المعنوية قياساً لمتوسط الأبوين، وللأب الأفضل لكافة الصفات المدروسة, وكان أبرزها الهجن ((Demere×Mouna, و((Anahiem×Mouna, و(قرن الغزال×Anahiem)؛التي تفوقت معنوياً على أفضل الأبوين عند أغلب الصفات؛ لذلك يمكن أن تعد هجن واعدة عند تفوقها في باقي الصفات الهامة؛ وهذا يُشجع على إنتاج هُجن الفليفلة محليًا،وزراعتها على النطاق التجاري لزيادةِ الإنتاج. كما تميزت هذه الهجن بمقدرة ائتلاف خاصة موجبة لأغلب الصفات المدروسة.أبدت الآباء((Almina, و(قرن الغزال), و(mouna) مقدرة ائتلاف عامة موجبة بدلالة إحصائية عالية لمعظم الصفات المدروسة.كما أبدت هجن هذه الآباء؛قيماً عالية ومعنوية للقدرة الخاصَّة على الائتلاف في معظم الصِفات المدروسَة؛ وعلى هذا يمكن استخدام هذه السُلالات للاستفادة منها في برامج تربية وَتحسين الفليفلة.ساهم كلا نمطي التفاعل الوراثي التراكمي واللا تراكمي في توريث إنتاجية النبات/كغ وحجم الثمار/سم3؛ لذا يمكن تحسين هاتين الصفتين إما بإنتاج الهجن أو بانتخاب أصناف ثابتة من نسلها، في حين تغلّب تأثير الفعل اللا تراكمي للمورثات كتعبير عن فعل التفوق و/أو السيادة في بقية الصفات، والتي ينحصر تحسينها بالاعتماد على إنتاج الهجن. The study was conducted in Tartous during 2013-2014. Five Hybrids of pepper were crossed by half diallil crosses to estimate heterosis, and evaluate combining ability of 10 hybrids for yield of plant and fruit traits.Most hybrids were characterized by high significant heterosis values for all studied traits compared to mid parents and better parents. Three hybrids (Anahiem×mouna) ,(Karn AL-ـgazelle× Mouna) and (Demere×Mouna) were characterized by high hybrid vigor compared to the best parent. They also demonstrated high positive specific combining ability (SCA) for most studied traits, and thus they may be promising hybrids. These results suggested that hybrid vigor is available for commercial production of pepper hybrid.Three parents )Almina),( Karn AL-gazelle), and (Mouna ,(have shown high positive general combining ability (GCA) for most of studied traits. The hybrids of these parents showed; high significant values for specific combining ability (SCA) in most studied traits, suggesting the importance of these parents to be used in breeding and improvement of pepper programs.Both types of gene action (additive and non- additive) had contributed in the inheritance of plant productivity / kg and size of the fruit / cm3, indicating the possibility of improving these qualities by producing the hybrids or selecting the fixed varieties, while the influence of non- additive controlled the inheritance of the other traits, reflecting the epistasis and/ or dominance genes action, and limiting its use to produce the hybrids only.